ANALYSIS OF THE EFFECTS OF HYPERTENSION IN CARDIO VASCULAR EVENTS AND QUALITY OF LIFE OF PATIENTS WITH CHRONIC KIDNEY DISEASE RECEIVING HEMODIALYSIS IN RSUP PERSAHABATAN - Diyana, Rusri
Hypertension is the cause and a complication of chronic kidney disease (CKD). It is also known as a risk factor of cardiovascular disease in hemodialised patients. A number of CKD symptoms may impact quality of life of CKD patients. The hypertension treatment in CKD patients is aimed to control blood pressure, as well as to reduce the risk of cardiovascular disease thus improving quality of life. The objective of this research is to understand the effects of high blood pressure medication in CKD patients receiving hemodialysis treatment in RSUP Persahabatan, particularly related to cardiovascular disease events and quality of life. The design of this study is cross seétional observational with concurrent medical record and patient daily status analyses during the period of October 2014 — Februmy 2015. Kidney Disease and Öüality of Life (KDQOLTM-36) was also used as a questionnaire tool. Subjects were CKD patients treated with hemodialysis and receiving anti hypertension drugs therapy, male and female, aged more than 18 years. Cardiovascular diseases events were stroke and chest pain as determined by physician's diagnosis based on physical examination, anamnesis and ECG results. The analysis result shows significant differences in the reduction of systolic (p=0.010) and diastolic (p=0.039) blood pressure in each group of antihypertension drug therapy. Furthermore, combination of 2 antihypertension drug therapy gives the most significant different in reduction of systolic and diastolic blood pressure (p=0.001). The effect of antihypertension drug therapy in cardiovascular events was insignificant, while combination of 3 antihypeftention drug therapy shows better average score of quality of life, the associated quality of life aspects were signs and symptoms, mental health and physical health but insignificant. There were significant relationships between cardiovascular events with maintained both systolic (p=0.019) and diastolic (p¯0.001) blood pressure. In addition, cardiovascular events was also highly associated with quality of life (p=0.001). The associated quality of life aspects were signs and symptoms that occurred due to the disease (p=0,034), burden of renal disease (p=0.019) and mental health (p 0.021). The combination of two antihypertension drug therapy shows as the most effective therapy in reducing blood pressure. Therefore, the therapy may control blood pressure. For each combination of antihypertension drug therapy, no significant difference was observed against.cardiovascular events and quality of life. Nevertheless, blood pressure control was significantly related with both outcomes. Accordingly, a maintained blood pressure could prevent and reduce the risk of cardiovascular disease in CKD, which leads to improve quality of life.